Telework and management: Technology for a more sustainable environment - Basso, R. B.F. [UNESP]; Battistelle, R. A.G. [UNESP]; Cavenaghi, V. [UNESP] (My University, 2013)
Several studies have been conducted in order to assess the volume of greenhouse gas emissions that cause climate change. A subject of great controversy that draws attention to the discomfort when there is discrepancy between the volume of resources extracted and marketed in relation to the capacity that nature has to replenish these resources. The increase in road transport vehicles and infrastructure of cities have collaborated with the unbalance in climatic conditions. Therefore, this study aims to take the technology not only as a tool to increase operational productivity, but also as a tool for sustainability. For the study, we broach the Telework, tripod of sustainability, environmental management, and approach to economic growth in the social strata. It should be noted that remote access to systems management arises as an important ally in reducing road traffic, reducing emissions, reducing movement of people, improvement in quality of life, and Telework is an example of tool that can generate gains social, environmental and economic. The analysis indicates that, despite efforts by a more sustainable environment, there is still a considerable gap between the economic performance of companies in relation to their social and environmental performance. On the other hand, information technology is viewed as an opportunity to increase productivity and profits, but not always directly related to projects more sustainable.
Keywords: Environmental management; Technological innovation; Telework; Tripod sustainability